Evolutionary motivations of status seeking and signaling in the context of travel - Santala, Maria (My University, 2024)
This thesis looks into the evolutionary motivations of status seeking and signaling in the context of travel. More specifically, the empirical research delved into status signaling, focusing on the two identified hierarchies, dominance and prestige, as well as two distinct travel groups, luxury travelers and backpackers. Firstly, the study demonstrates that individuals are inclined to travel to destinations where they feel a sense of belonging, using their travel choices to signal aspects of their self-identity. Additionally, the empirical analysis reveals distinct status signaling strategies employed by luxury travelers and backpackers, with luxury travelers favoring dominance-based behaviors such as conspicuous consumption, while backpackers lean more towards prestige-based behaviors such as showcasing knowledge and skills. These findings support existing evolutionary psychology theories and highlight the importance of considering diverse consumer groups and their evolving behavior in tourism management. Practically, the research offers insights for tourism managers to tailor their marketing strategies and destination offerings to align with the preferences and values of specific travel groups, thereby enhancing visitor satisfaction and fostering stronger connections between travelers and destinations.
Keywords: self-identity, self-congruity, evolutionary psychology, status, dominance, prestige, travel, luxury travel, backpacking